The search for the North Pole = or, Life in the great white world. A complete and connected story of Arctic explorations, superbly illustrated from real scenes. Replete with anecdote, incident, thrilling adventure, and intensely interesting information. The book with a purpose consecrated to further polar investigation - Baldwin, Evelyn Briggs, 1862-1933. (Chicago : [s.n.], 1896)
Author native of Edna, Kan. (Cf. Edna centennial book) Mode of access: Internet.